HOW DOES AUDITORY INFORMATION INFLUENCE OBSERVERS' PERCEPTION DURING THE EVALUATION OF COMPLEX SKILLS? - Frederike Veit (University of Ljubljana Press (Založba Univerze v Ljubljani), 2020)
Perceiving and gathering information from the environment are essential abilities of humans, especially in sports. An individual's perception of aspects such as the surrounding conditions or the movements of other athletes can be decisive for a successful performance. The question that arises is whether an individual's level of expertise affects his or her ability to use task-specific information. Furthermore, it should be determined whether the type of information that is gathered differs across people with different sport-specific experiences. The aim of the study was to investigate the role of auditory information in the observation and evaluation of complex skills in gymnastics. Participants with different amounts of experience were asked to estimate the duration of flight phases in straight-back somersaults on the floor under manipulated auditory conditions. The results of the current study show that participants with no specific experience in gymnastics performed worse than participants with visual or motor experiences. Additionally, the current gymnasts outperformed the other participants. One could speculate that current gymnasts benefit from their motor experiences, which lead to improved perceptual sensitivity and a better ability to identify differences between two cues. In conclusion, it could be enriching to take the auditory information into account in motor learning tasks.